2007
DOI: 10.1002/jsfa.2807
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid pigments in kale are influenced by nitrogen concentration and form

Abstract: The objective of these experiments was to investigate the effects of N rate and form on the accumulation of lutein, β-carotene and chlorophyll pigments in the leaf tissues of kale. Winterbor, Toscano and Redbor kale cultivars were greenhouse grown using nutrient solution culture. In the first study, N treatments were 6, 13, 26, 52 and 105 mg L −1 at a constant 1 NH 4 -N:3 NO 3 -N ratio. On a fresh weight basis, plant pigment concentrations (lutein, β-carotene and chlorophylls) were not affected by N rate. When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
58
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 35 publications
(52 reference statements)
13
58
3
1
Order By: Relevance
“…The amino acid composition of seaweeds is original and different from that of land plants (Cerna 2011). The synthesis and tissue concentration of high-value components of industrial interest within the biomass (i.e., amino acids, pigments, and antioxidants) increase with nitrogen availability (Gerard 1988;Kopsell et al 2007), and most photosynthetic pigments (e.g., chlorophylls) also increase with decreasing light availability (Bruhn and Gerard 1996;Gomez and Wiencke 1998;Roleda and Dethleff 2011). Concentrations of pigments, such as carotenoids, respond to light availability in a more complex manner, reflecting their accessory as well as photoprotective functions.…”
Section: Introductionmentioning
confidence: 97%
“…The amino acid composition of seaweeds is original and different from that of land plants (Cerna 2011). The synthesis and tissue concentration of high-value components of industrial interest within the biomass (i.e., amino acids, pigments, and antioxidants) increase with nitrogen availability (Gerard 1988;Kopsell et al 2007), and most photosynthetic pigments (e.g., chlorophylls) also increase with decreasing light availability (Bruhn and Gerard 1996;Gomez and Wiencke 1998;Roleda and Dethleff 2011). Concentrations of pigments, such as carotenoids, respond to light availability in a more complex manner, reflecting their accessory as well as photoprotective functions.…”
Section: Introductionmentioning
confidence: 97%
“…Once S supply is adequate, however, minimal N applications resulted in highest glucoraphanin content in broccoli (Table 1) (Jones et al, 2007), but N application rates that optimized glucoraphanin content in broccoli resulted in a significant decline in head weight (Jones et al, 2007) In a study with higher N application rates (50-600 kg ha À1 ), Omirou et al (2009) found glucoraphanin content in broccoli florets was maximized with a mid-range N application of 250 kg ha À1 . Growth stress caused by limited N also resulted in enhanced glucosinolate synthesis in pak choi (Shattuck & Wang, 1994), watercress (Kopsell et al, 2007a(Kopsell et al, , 2007b, and cabbage (Rosen et al, 2005) (Table 1). Jones et al (2007) postulated that poor N availability in broccoli florets may indirectly result in an increased availability of methionine for glucosinolate production, as suggested by Dick-Hennes and Buning-Pfaue (1992).…”
Section: Glucosinolatesmentioning
confidence: 94%
“…The most relevant reference is cited. Shattuck and Wang (1994) 14-224 mg L À1 14 mg L À1 Watercress Kopsell et al (2007aKopsell et al ( , 2007b 6-106 mg L À1 56 mg L À1…”
Section: Flavonoids and Other Phenolicsmentioning
confidence: 99%
“…Nitrogen (N) fertilizers can increase the contents of crude protein (CP) and carotenoids (b-carotene) in forages (Kopsell et al 2007;King et al 2012). The contents of CP and carotenoids in grass forages are higher in the early reproductive stage compared with more advanced stages (King et al 2012).…”
Section: Introductionmentioning
confidence: 99%